Evaluation of the occurrence of phthalates in plastic materials used in food packaging - Perestrelo, Rosa (2021)
Phthalates are multifunctional synthetic chemicals found in a wide array of consumer and industrial products, mainly used to improve the mechanical properties of plastics, giving them flexibility and softness. In the European Union, phthalates are prohibited at levels greater than 0.1% by weight in most food packaging. In the current study, headspace solid-phase microextraction (HS SPME) combined with gas chromatography-mass spectrometry (GC-MS) was optimized, through the multivariate optimization process, and validated to evaluate the occurrence of four common phthalates, di-iso-butyl phthalate (DIBP), butyl-benzyl phthalate (BBP), di-n-octyl phthalate (DOP), and 2,2,4,4-tetrabromodiphenyl (BDE), in different food packaging. The best extraction efficiency was achieved using the polydimethylsiloxane/divinylbenzene (PDMS/DVB) fiber at 80 ◦C for 30 min. The validated method showed good linearity, precision (RSD < 13%), and recoveries (90.2 to 111%). The limit of detection (LOD) and of quantification (LOQ) ranged from 0.03 to 0.08 µg/L and from 0.10 to 0.24 µg/L, respectively. On average, the phthalates concentration varied largely among the assayed food packaging. DIBP was the most predominant phthalate in terms of occurrence (71.4% of analyzed simples) and concentration (from 3.61 to 10.7 µg/L). BBP was quantified in only one sample and BDE was detected in trace amounts (<LOQ) in only two samples.